Afro-Palaearctic migrant birds rid themselves of haemoparasite infections when breeding in the temperate zone - Wojciech Bielański (Scientific Reports)
Abstract In migratory passerines, the prevalence and parasitaemia of blood parasites often increase towards the end of the breeding season. Consequently, post-breeding migration to winter quarters can be seen as a strategy to avoid the rising pathogen pressure during this time (migratory escape). I studied haemoparasite infections in sedge warblers (Acrocephalus schoenobaenus) inhabiting natural wetlands in southern Poland, examining the same individuals just after their arrival from wintering grounds, and again during incubation or nestling feeding. The birds were found to be infected more often immediately after arrival than during subsequent sampling. Parasitaemia also decreased significantly as the season progressed. The health status of individuals appeared to improve during the breeding season, whereas the higher level of parasitaemia just after arrival suggests that infections had occurred earlier, on the wintering grounds or during migratory stopovers.